Minnesota State Parks and Trails’ use of Facebook to Communicate Health and Safety Information During the COVID-19 Pandemic - Garrett M Steede; Sahil S Kamat (Journal of Applied Communications, 2023)
During the COVID-19 pandemic, state park visitation increased to levels above previous years. While navigating the pandemic, natural resource communicators took to social media to communicate about how COVID-19 was impacting park services and operations. We examined how the Minnesota State Parks and Trails (MSPT) engaged in health communication using Facebook over the first two years of the COVID-19 pandemic. We used quantitative content analysis to measure content and engagement on the N = 105 posts made by the MSPT from 2020 - 2022 regarding COVID-19. Results provide an understanding as to how natural resource communicators engaged in health communication during a pandemic. While natural resource communicators were tasked with communicating about an unfamiliar issue, appropriate science communication principles should be incorporated into all science communication plans. MSPT and communication staff at other state parks agencies should ensure they are prepared to communicate about health issues in times of crisis.
Keywords: COVID; health communication; natural resources; social media; state parks